Prevalence of undernutrition in children with cancer in low-income and middle-income countries: a systematic review - Gertjan Kaspers; Minke Huibers; Nthongase Makamo; Sterre Schoon; Nmazuo Ozuah; Elena J Ladas (BMJ Global Health)
Background Undernutrition is linked to decreased survival in childhood cancer. However, its global impact remains unclear, and childhood cancer is not recognised as a high-risk factor in WHO nutrition guidelines. This systematic review quantifies the prevalence and clinical outcomes of undernutrition among children with cancer in low-income and middle-income countries (LMICs), highlighting the global burden and impact on children with cancer.Methods Ovid Medline, EMBASE, Cochrane and Web of Science databases were searched until September 2024. Key search terms included “developing countries”, “neoplasm”, “child” and “undernutrition”. LMICs were classified by the World Bank data. Undernutrition was defined by the WHO and includes wasting, stunting and underweight.Findings Data from 21 646 children across 88 studies in 23 countries revealed prevalence rates ranging from 6.1% in China to 88.4% in South Africa. Nutritional assessments predominantly relied on weight-based indicators (57.0%), with mid-upper arm circumference used in 17.0% and combined methods in 27.0%. Older children (>5 years) showed a trend towards higher undernutrition prevalence rates compared with younger children. Undernutrition was associated with deteriorating outcomes in 7 out of 11 studies (p<0.05).Interpretation Our findings show the substantial burden of undernutrition among children with cancer in LMICs. Childhood cancer should be recognised as a high-risk factor in international nutrition guidelines, in order to promote equitable care and improve survival rates. Targeted intervention studies are needed, supporting the WHO’s goal of 60% survival for common and curable childhood cancer types by 2030.